Lupus-associated vasculitis manifesting as acute appendicitis in a 16 year old girl - Hoda Syed A; Cellini Christina; Spigland Nitsana (BMC, 2008)
Abstract A 16 year old female with systemic lupus erythematosus presents with acute appendicitis. Final pathologic analysis of the appendix describes a lupus-associated vasculitis.